Hydration Structures and Dynamics of Ga3+ Ion Based on Molecular Mechanics Molecular Dynamics Simulation (Classical DM) - Muhammad Syaekhul Anam; S. Suwardi (Indonesian Journal of Chemistry and Environment, 2022)
The structure and hydration dynamics of Ga3+ ion have been studied using classical Molecular Dynamics (MD) simulations. The data collection procedure includes determining the best base set, constructing 2-body and 3-body potential equations, classical molecular dynamics simulations based on 2-body potentials, classical molecular dynamics simulations based on 2-body + 3 potential-body. The trajectory file data analysis was done to obtain structural properties parameters such as RDF, CND, ADF, and dynamic properties, namely the movement of H2O ligands between hydrations shells.     The results of the research indicated that the hydration complex structure of Ga(H2O)83+ and Ga(H2O)63+ was observed in molecular dynamics simulations (MM-2 body) and (MM-2 body + 3-body), respectively. The movement of H2O ligands occurs between the first and second shell or vice versa in the MD simulation of MM-2 bodies but does not occur in MD simulations of (MM-2 bodies + MM-3 bodies). Therefore, the water ligands in the first hydrated shell are stable.